Macadamia nutshell powder grafted with 1,5’-diphenylcarbizide for enhanced removal of Cr(VI ) from aqueous solution - Maremeni, Londolani Charity (My University, 2018)
Agricultural waste such as Macadamia nutshells are currently receiving more attention for removal of hexavalent chromium (Cr(VI)). However, they have low adsorption capabilities when used in their raw form. In this study, the efficiency of using Macadamia nutshell powder modified with different concentrations of hydrogen peroxide, grafted with 1,5’-diphenylcarbizide (DPC) for the removal of hexavalent chromium from aqueous solution was explored. The effects of various parameters controlling adsorption of Cr(VI) onto Macadamia adsorbents such as initial concentration, contact time, adsorbent concentration and pH were investigated. The optimal operating parameters for Macadamia nutshells treated with hydrogen peroxide (MHP) adsorbents were determined to be 75 mg/L, 3 h, 0.1 g and pH 1. The optimal operating parameters for Macadamia nutshells treated with hydrogen peroxide and grafted with 1,5’-diphenylcarbizide (MHPD) were determined to be 150 mg/L, 1 h, 0.1 g and pH 3. Fourier transform infrared (FTIR) spectroscopy of the adsorbents revealed that treated MHP showed amino groups attached to the adsorbents. Thermogravimetric analysis (TGA) revealed that the grafted material lowered the thermal stability from 180◦C to 300◦C due to volatile nature of DPC. The surface of the MHPD materials was rough due to grafting. The results showed that the 1,5’-diphenylcarbazide treatment improved the removal efficiency of Cr(VI).
M. Tech (Department of Chemistry, Faculty of Applied and Computer Sciences) Vaal University of Technology.
Keywords: Macadamia, hexavalent chromium (Cr(VI)), hydrogen peroxide, thermogravimetric; Macadamia nut.; Water chemistry.